HIV and Mediterranean Zoonoses: A Review of the Literature - Ylenia Russotto; Cristina Micali; Giovanni Francesco Pellicanò; Giuseppe Nunnari; Emmanuele Venanzi Rullo (Infectious Disease Reports, 2022)
A zoonosis is an infectious disease that has jumped from a non-human animal to humans. Some zoonoses are very common in the Mediterranean area and endemic in specific regions, so they represent an important problem for public health. Human Immunodeficiency Virus (HIV) is a virus that has originated as a zoonosis and is now diffused globally, with the most significant numbers of infected people among the infectious diseases. Since the introduction of antiretroviral therapy (ART), the history for people living with HIV (PLWH) has changed drastically, and many diseases are now no different in epidemiology and prognosis as they are in not-HIV-infected people. Still, the underlying inflammatory state that is correlated with HIV and other alterations related to the infection itself can be a risk factor when infected with other bacteria, parasites or viruses. We reviewed the literature for infection by the most common Mediterranean zoonoses, such as Campylobacter, Salmonella, Brucella, Rickettsia, Borrelia, Listeria and Echinococcus, and a possible correlation with HIV. We included Monkeypox, since the outbreak of cases is becoming a concern lately. We found that HIV may be related with alterations of the microbiome, as for campylobacteriosis, and that there are some zoonoses with a significant prevalence in PLWH, as for salmonellosis.